Optimasi Tata Letak Fasilitas Divisi Jok PT XYZ Menggunakan Metode Activity Relationship Chart - Utami, Tasya Khamila; Hartono, Ridwan (Metode : Jurnal Teknik Industri, 2026)
The initial facility layout condition in the Seat Division of PT XYZ remains suboptimal, characterized by the accumulation of seats in the assembly and finishing area and an excessive material transfer distance, reaching 86.88 meters. This situation results in cramped production space and hinders overall work efficiency. This study aims to analyze the current facility layout and provide a layout improvement proposal to ensure the production process is both effective and efficient. The Activity Relationship Chart (ARC) method was adopted to analyze the functional closeness relationships among the seven departments, integrating material flow requirements with non-material factors such as noise and supervision. The resulting ARC matrix was then processed using the BLOCPLAN software to design three alternative layout proposals. The efficiency of each proposal was quantitatively evaluated by calculating the Euclidean Distance between department centroids for the main process flow. The comparative analysis of material transfer distance showed that Proposed Layout Two is the best alternative, with a total distance of 57.56 meters (measured using the Euclidean Distance method). This proposal is capable of reducing the material transfer distance by 29.32 meters, or approximately 33.7%, from the initial layout. This layout improvement is expected to optimize space utilization, minimize material accumulation, and streamline the workflow.